Narrative Techniques in Ngugi wa Thiong’o’s Dreams in a Time of War - DIGUMEFELE, Marie-Jeanne NGELEMA; Kisangani, ISP-; Recherche, Domaine de (IJRDO- Journal of Educational Research, 2022)
The study on analysis of narrative Techniques in Ngugi wa Thiong’o’s Dreams in a Time of War consists of deepening stylistic studies of the and finally to have an idea on the sort of language used in the work. The style of Ngugi wa Thiong’o is characterized by usage of simple sentences and short, long even complex, usage the flashback, usage the real names and a forest of figures of style.